The viability of poly (chlorotrifluoroethylene-co-vinylidene fluoride) as an oxidiser in extrudable pyrotechnic compositions - Focke, Walter Wilhelm (University of Pretoria, 2017)
Dissertation (MEng)--University of Pretoria, 2017.